2018
DOI: 10.11114/jets.v6i3.3048
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Therapeutic Recreational Gymnastic Exercise on Basic Motor Skills of Hearing-Impaired Children Aged Between 6 and 9 Years

Abstract: Purpose: The purpose of the current study is to investigate the impact of therapeutic recreational gymnastic exercises on basic motor skills of hearing-impaired children aged between 6-9 years.Material and Method: 18 students (12 boys; 6 girls) between the ages of 6-9 years participated in the study. 9 of these students were determined as experimental group (3 girls; 6 boys), and the other 9 were determined as control group (3 girls; 6 boys). Before and after the trainings, gross motor development tests (25m. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Their idea of an ideal person does not match their self-concept. Similar data were obtained by other authors for school students and higher eduction students with hearing, vision, and musculoskeletal impairments and other nosology's (Demirel, 2018;Nemcek, 2017). This calls for these provisions to be taken into account when designing a training program.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Their idea of an ideal person does not match their self-concept. Similar data were obtained by other authors for school students and higher eduction students with hearing, vision, and musculoskeletal impairments and other nosology's (Demirel, 2018;Nemcek, 2017). This calls for these provisions to be taken into account when designing a training program.…”
Section: Discussionsupporting
confidence: 81%
“…The problem of organizational and methodological approaches to adaptive physical education of students with hearing impairment has been addressed in the scientific literature (Rychok, 2018). Previous studies have shown the effectiveness of using recreational activities to develop physical abilities of children with hearing impairment (Demchuk & Vypasnyak, 2016;Demirel, 2018). Correction of physical and psychological states and motor disorders of children and young people with hearing impairment by means of adaptive physical culture has been described in the studies (Solish Perry & Minnes, 2018;Palmer, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Hearing-impaired children can be affected from daily life activity depending on their age, gender and hearing loss degree. The fact that their daily life is affected in hearing-impaired children because of loss of static and dynamic balance [7].…”
Section: Introductionmentioning
confidence: 99%
“…When disabled individuals are lead to sports, it is seen the positive developments in their physical and physiological capacities [7]. Training program improves hearing impaired children's motor skills, balance and health related quality of lifestyle [16].…”
Section: Introductionmentioning
confidence: 99%